PELATIHAN AKUNTANSI UTANG OBLIGASI BAGI SISWA - Henny; Steven; Christiano Cannavaro (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
Education is one of the factors in increasing quality human resources. Therefore, the role of education is very important in today's society. In producing quality education, it requires experts (teachers), a relevant curriculum, and the availability of facilities and infrastructure. In addition, skills and abilities are needed from experts in providing explanations of the material presented. To help solve educational problems, especially education in the field of accounting, the Mahkota Kasih Insani Foundation invites accounting lecturers from the Faculty of Economics and Business to carry out community service activities. This activity is a solution that can be provided in order to help students of the Mahkota Kasih Insani Foundation understand accounting, especially the accounting treatment of bonds payable with the help of support and funds from the Institute for Research and Community Service, Universitas Tarumanagara. Based on this activity, students can develop their abilities. The training method is used in implementing this activity. The output obtained from this activity is a mandatory output in the form of publication of articles in community service journals as proof of having carried out community service at the Mahkota Kasih Insani Foundation, and the general public can see the articles in the journal, so that they are motivated to help more orphanages throughout Indonesia. Another output generated from this activity is an additional output in the form of intellectual property rights to obtain legal protection for copyright from community service activities. The implementation of community service activities at the Mahkota Kasih Insani Foundation began with a pre-test, providing material presentation, continued by discussing practice questions, then from the practice questions given, a discussion was carried out, after which a question and answer session was opened and ended with a post-test and evaluation of the implementation of activities and taking a group photo at the Mahkota Kasih Insani Foundation. Education is one of the factors in increasing quality human resources. Therefore, the role of education is very important in today's society. In producing quality education, it requires experts (teachers), a relevant curriculum, and the availability of facilities and infrastructure. In addition, skills and abilities are needed from experts in providing explanations of the material presented. To help solve educational problems, especially education in the field of accounting, the Mahkota Kasih Insani Foundation invites accounting lecturers from the Faculty of Economics and Business to carry out community service activities. This activity is a solution that can be provided in order to help students of the Mahkota Kasih Insani Foundation understand accounting, especially the accounting treatment of bonds payable with the help of support and funds from the Institute for Research and Community Service, Universitas Tarumanagara. Based on this activity, students can develop their abilities. The training method is used in implementing this activity. The output obtained from this activity is a mandatory output in the form of publication of articles in community service journals as proof of having carried out community service at the Mahkota Kasih Insani Foundation, and the general public can see the articles in the journal, so that they are motivated to help more orphanages throughout Indonesia. Another output generated from this activity is an additional output in the form of intellectual property rights to obtain legal protection for copyright from community service activities. The implementation of community service activities at the Mahkota Kasih Insani Foundation began with a pre-test, providing material presentation, continued by discussing practice questions, then from the practice questions given, a discussion was carried out, after which a question and answer session was opened and ended with a post-test and evaluation of the implementation of activities and taking a group photo at the Mahkota Kasih Insani Foundation. ABSTRAK Pendidikan merupakan salah satu faktor dalam meningkatkan sumber daya yang bermutu. Oleh karena itu, peran pendidikan sangat penting di dalam kehidupan masyarakat saat ini. Dalam menghasilkan pendidikan yang berkualitas, dibutuhkan tenaga ahli (pengajar), kurikulum yang relevan, serta tersedianya sarana dan prasarana. Selain itu, dibutuhkan keterampilan dan kemampuan dari tenaga ahli dalam memberikan penjelasan atas materi yang disampaikan. Untuk membantu menyelesaikan permasalahan pendidikan terutama pendidikan di bidang akuntansi, maka Yayasan Mahkota Kasih Insani mengundang dosen akuntansi Fakultas Ekonomi dan Bisnis untuk melakukan kegiatan pengabdian kepada masyarakat. Kegiatan ini merupakan solusi yang yang dapat diberikan dalam rangka membantu siswa Yayasan Mahkota Kasih Insani dalam memahami akuntansi terutama perlakuan akuntansi utang obligasi dengan bantuan dukungan dan dana dari Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Tarumanagara. Berdasarkan kegiatan ini siswa dapat mengembangkan kemampuan yang dimiliki. Metode pelatihan digunakan dalam pelaksanaan kegiatan ini. Luaran yang didapatkan dari kegiatan ini adalah luaran wajib berupa publikasi artikel di jurnal pengabdian kepada masyarakat sebagai bukti sudah melakukan pengabdian kepada masyarakat di Yayasan Mahkota Kasih Insani, dan masyarakat umum dapat melihat artikel di jurnal tersebut, sehingga termotivasi membantu lebih banyak panti asuhan di seluruh Indonesia. Luaran lain yang dihasilkan dari kegiatan ini adalah luaran tambahan berupa hak kekayaan intelektual guna memperoleh perlindungan secara hukum atas hak cipta dari kegiatan pengabdian kepada masyarakat. Pelaksanaan kegiatan pengabdian kepada masyarakat di Yayasan Mahkota Kasih Insani diawali dengan pre test, memberikan pemaparan materi, dilanjutkan dengan membahas latihan soal, kemudian dari latihan soal yang diberikan, dilakukan pembahasan, setelah itu dibuka sesi untuk tanya jawab dan diakhiri dengan post test serta evaluasi pelaksanaan kegiatan dan melakukan foto bersama di Yayasan Mahkota Kasih Insani.